2014
DOI: 10.3109/01658107.2014.926943
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Nonarteritic Anterior Ischaemic Optic Neuropathy: A Study with Optical Coherence Tomography

Abstract: Nonarteritic anterior ischemic optic neuropathy (NA-AION) is the most common nonglaucomatous optic neuropathy in adults over 50 years of age. It is usually related to cardiovascular risk factors. The primary objective of this study was to evaluate choroidal thickness in patients with chronic NA-AION, and the secondary objective was to evaluate macular thickness in these patients. This cross-sectional study compared two groups: group 1 included 20 eyes of 20 patients with chronic NA-AION, and group 2 included 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(58 reference statements)
0
17
1
1
Order By: Relevance
“…It has been reported that choroidal changes may be involved in retinal and optic nerve diseases such as chronic NAION because the choroid plays a vital role in supplying oxygen and nutrition to the outer layers of the retina, or RPE, and to the pre-laminar portion of the ONH. 2,17 However, one study has investigated this relationship between NAION and CT in patients who have acute NAION. 19 Our study results demonstrate that the groups of patients with acute and chronic NAION have no significant difference in terms of CTs compared with the control group and the internal control generated from the unaffected eyes of these NAION patients with unilateral disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that choroidal changes may be involved in retinal and optic nerve diseases such as chronic NAION because the choroid plays a vital role in supplying oxygen and nutrition to the outer layers of the retina, or RPE, and to the pre-laminar portion of the ONH. 2,17 However, one study has investigated this relationship between NAION and CT in patients who have acute NAION. 19 Our study results demonstrate that the groups of patients with acute and chronic NAION have no significant difference in terms of CTs compared with the control group and the internal control generated from the unaffected eyes of these NAION patients with unilateral disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, taking OCT measurements at one selected point and comparing them with each other is not the most precise method for determining CTs, since these measurements, which are performed manually, may be affected by local irregularities of the choroid-scleral boundary. 17,21,22 Therefore, to reduce the risk of mistakes caused by this, we used three horizontal sections for the CT measurements, which were evaluated on these sections at three points, and used the average of these three measurements for comparisons. Also, the development of automatic software for CT measurements will, in the future, help to improve the accuracy of these measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations